MISKONSEPSI PADA KONSEP SUHU DAN KALOR - Siti Kamilah, Dendy (Loka Diklat Keagamaan Bandar Lampung, 2023)
Students’ ideas that different from scientific concepts are called misconception. Misconception is an obstacle in learning physics. This paper provides a review of national journal articles about misconception of heat and temperature that have been published between 2018-2023. The result is discovery of many misconceptions in each sub-concept heat and temperature such as thermal equilibrium, quantity of heat, phase changes, thermal expansion, anomaly of water, heat transfer and Black principle. This study will be beneficial for educator and researcher in making lesson plan and test instrument to remediate and identify misconception.